Storing carbon in leaf lipid sinks enhances perennial ryegrass carbon capture especially under high N and elevated CO2. (3rd November 2019) - Beechey-Gradwell, Zac; Cooney, Luke; Winichayakul, Somrutai; Andrews, Mitchell; Hea, Shen Y; Crowther, Tracey; Roberts, Nick
Abstract : Engineering a novel lipid carbon sink into ryegrass leaves induced leaf physiological changes that increased overall carbon capture and growth, and enhanced the photosynthetic response to elevated atmospheric CO2 exposure. Abstract: By modifying two genes involved in lipid biosynthesis and storage [cysteine oleosin (cys-OLE)/diacylglycerol O -acyltransferase (DGAT)], the accumulation of stable lipid droplets in perennial ryegrass ( Lolium perenne ) leaves was achieved. Growth, biomass allocation, leaf structure, gas exchange parameters, fatty acids, and water-soluble carbohydrates were quantified for a high-expressing cys-OLE/DGAT ryegrass transformant (HL) and a wild-type (WT) control grown under controlled conditions with 1–10 mM nitrogen (N) supply at ambient and elevated atmospheric CO2 . A dramatic shift in leaf carbon (C) storage occurred in HL leaves, away from readily mobilizable carbohydrates and towards stable lipid droplets. HL exhibited an increased growth rate, mainly in non-photosynthetic organs, leading to a decreased leaf mass fraction. HL leaves, however, displayed an increased specific leaf area and photosynthetic rate per unit leaf area, delivering greater overall C capture and leaf growth at high N supply. HL also exhibited a greater photosynthesis response to elevated atmospheric CO2 . We speculate that by behaving as uniquely stable microsinks for C, cys-OLE-encapsulated lipid droplets can reduce feedback inhibition of photosynthesis and drive greater C capture. Manipulation of many genes and gene combinations has been used to increase non-seed lipid content. However, the cys-OLE/DGAT technology remains the only reported case that increases plant biomass. We contrast cys-OLE/DGAT with other lipid accumulation strategies and discuss the implications of introducing lipid sinks into non-seed organs for plant energy homeostasis and growth.